KAJIAN KONSENTRASI EKSTRAK TANAMAN TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PADI (Oryza sativa L.) - andi fajarwanto; Siswadi Siswadi; Dewi Ratna Nurhayati (Innofarm:Jurnal Inovasi Pertanian, 2020)
Research on the study of the concentration of plant extracts on the growth and yield of rice plants was carried out in April - July 2020, located in Pare Village, Mondokan District, Sragen Regency with an altitude of 150 masl with grumosol soil type. This study aims: to see the effect of plant extracts on the growth and yield of rice plants, to measure the best extracts on the growth and yield of rice plants. This study used a randomized group (RAKL) single factor plant extract with various concentrations that resulted in 10 different treatments. A0K0: without presenting plant extracts, A1: Bamboo shoot extract, A2: Banana hump extract, A3: Onion extract, K1: 20ml / l concentration, K2: 40ml / l concentration, K3: 60ml / l concentration. The treatment was repeated 3 times in order to get 30 experimental experiments. The experimental unit of a treatment consisting of 4 clumps of plants. Observations were made on the treatment plots. To see no effect of the effect of plant extracts, a test through analysis of variance was used. Meanwhile, to determine the significance of the treatment, the Duncan test was used at level of 5%. The results showed (1)Bamboo shoots, banana weevil and shallot plant extracts were able to increase the number of tillers per clump by 19% compared to the control but did not affect plant height, leaf color, panicle length, number of grains per clump, grain weight per clump and weight of 1000 grains . (2)Bamboo shoots, banana weevil and shallot plant extracts were able to increase the number of clump panicles by 23% compared to the control but did not affect plant height, leaf color, panicle length, number of grains per clump, grain weight per clump and weight of 1000 grains.